Machining of hard-to-cut AISI 4462 duplex stainless steel with an environmentally friendly approach with vortex tube - Sönmez, Fikret (Strojniški vestnik, 2023)
Machining is a manufacturing process that can be used to produce precision machine parts and has many advantages. The first is the ability to achieve superior surface quality. Tool wear is an inevitable phenomenon that occurs during machining. It is affected by many machining conditions; therefore, this process needs to be monitored and controlled. In this study, tool wear and surface roughness tests were carried out on AISI 4462 duplex stainless-steel materials, known to be a hard-to-cut material. For this purpose, tool wear and surface roughness analyses were implemented by using the environmentally friendly vortex tube cooling system in addition to wet turning conditions for the first time. For both methods, experiments were conducted at a 1 mm depth of cut, 120 m/min cutting speed, and 0.1 mm/rev feed with a 90 mm cutting length for each pass. Both tool wear and surface roughness were examined at the end of each pass. The analysis showed that wet turning gave better results in terms of tool life (19.8 minutes of tool life) compared to 11.1 minutes of tool life in vortex turning. In contrast, the surface roughness values differed up to two times in some experiments, and the vortex tube experiments gave better surface roughness values in all passes. In addition, the vortex tube experiments showed less built-up-edge (BUE) formation than the wet-turning experiments.
Keywords: dupleksno nerjavno jeklo; duplex stainless steel; machining; obdelava z odrezavanjem; obstojnost orodja; površinska hrapavost; surface roughness; tool life; vortex tube; vrtinčna cev